One-step synthesis of gradient gadolinium ironhexacyanoferrate nanoparticles: a new particle design easily combining MRI contrast and photothermal therapy1. Issue 12 (28th March 2015) - Li, Yichen; Li, Carissa H.; Talham, Daniel R.
<x xml:space="preserve">Abstract</x> The newly developed concentration gradient gadolinium-based Prussian blue particles provide a new particle platform for enhanced performance as MRI and photothermal therapy agents.